2019
DOI: 10.1016/j.cej.2019.122250
|View full text |Cite
|
Sign up to set email alerts
|

Slurry loop tubular membrane reactor for the catalysed aerobic oxidation of benzyl alcohol

Abstract: A slurry loop reactor was designed for the aerobic oxidation of benzyl alcohol. • A tubular membrane was incorporated for safe and controlled oxygen delivery. • Similar oxidation rate was achieved to that of a conventional autoclave reactor. • The addition of a crossflow filter inside the loop allowed for continuous operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(86 reference statements)
1
6
0
Order By: Relevance
“…Aerobic oxidations of alcohols were performed using a 1 wt% Au-Pd/TiO 2 catalyst (Scheme 2). Other works report the use of this catalyst, 46,55,57 including Hutchings’ group, who found that the addition of Au to Pd nanocrystals enhanced the selectivity to aldehydes in the aerobic oxidation of alcohols, owing to the core-shell structure that Au creates with Pd. 57 The catalyst was supplied by Johnson Matthey and was prepared by co-impregnating HAuCl 4 ·3H 2 O (Johnson Matthey) and PdCl 2 (Johnson Matthey) onto TiO 2 (Evonik, P25) in a 1 : 19 Au-to-Pd weight ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Aerobic oxidations of alcohols were performed using a 1 wt% Au-Pd/TiO 2 catalyst (Scheme 2). Other works report the use of this catalyst, 46,55,57 including Hutchings’ group, who found that the addition of Au to Pd nanocrystals enhanced the selectivity to aldehydes in the aerobic oxidation of alcohols, owing to the core-shell structure that Au creates with Pd. 57 The catalyst was supplied by Johnson Matthey and was prepared by co-impregnating HAuCl 4 ·3H 2 O (Johnson Matthey) and PdCl 2 (Johnson Matthey) onto TiO 2 (Evonik, P25) in a 1 : 19 Au-to-Pd weight ratio.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that gas delivery is disconnected from the liquid fluid dynamics in the annulus, membranes can be adopted. The use of membranes in flow reactors have gained popularity owing to their ability to provide control of exothermic gas‐liquid reactions, by distributing and dosing gaseous reactants while physically separating the two reacting phases 41–44 …”
Section: Introductionmentioning
confidence: 99%
“…The use of membranes in flow reactors have gained popularity owing to their ability to provide control of exothermic gasliquid reactions, by distributing and dosing gaseous reactants while physically separating the two reacting phases. [41][42][43][44] Wro nski et al demonstrated a Taylor-vortex membrane device that consisted of a cylindrical rotor inside a stationary tubular ceramic membrane. 45 Gas was pressurized outside the membrane and, depending on its pressure with respect to the liquid, diffusion or bubbling could be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Dense, hydrophobic, gas-permeable membranes that show high liquid pressure breakthrough, like the Teflon AF-2400 have recently attracted considerable interest, due to its high permeability to light gases and its chemical inertness [30,31]. Teflon AF-2400 has been employed in a variety of gas-liquid and gas-liquid-solid reactions [32][33][34][35][36][37]. First introduced by the group of Ley [38], Teflon AF-2400 has been employed in a tube-in-tube configuration for both homogeneous and heterogeneous continuous hydrogenations using hydrogen pressurised outside and the reacting liquid flowing inside the membrane [33].…”
Section: Introductionmentioning
confidence: 99%